Preconditioning of fresh cocoa beans prior to fermentation to improve quality: a commercial approach - Mamat bin Said (MARDI, Hilir Perak (Malaysia). Cocoa dan Coconut Research Div.) (2013)
Studies were carried out on a commercial scale at Blenheim Estate of Kuril Plantations Sdn. Bhd., Lower Perak to reduce acid content, and consequently improve cocoa flavour. The method was developed based on the concept of pulp reduction of the wet beans by preconditioning prior to fermentation. Techniques adopted were pressing, air-blasting, pressing followed by air-blasting, and a short post-harvest storage followed by pressing and air-blasting prior to five days fermentation. Fermentation was carried out in shallow boxes with one turning on the third day. Although the normal practice of overnight storage of wet beans caused a reduction in pulp volume and content, it was found detrimental to the cocoa quality due to accumulation of lactic acid. Therefore the practice was discontinued. Our studies indicated that the pulp preconditioning through a combination of short pod storage and pressing followed by air-blasting gave a higher chocolate flavour strength than the beans fermented under normal estate practice. Besides an improvement in chocolate flavour, there was also a lower shell content and a better bean count.